2017
DOI: 10.33425/2639-9474.1017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Parental Compliance with Routine Childhood Immunization Schedule in Nassarawa State, Nigeria

Abstract: Background: Vaccine preventable diseases are major causes of child mortality which could have been prevented by routine immunization. Many children are not completely immunized due to non-compliance by their parents.Aim: This study explored the determinants of parental compliance with routine childhood immunization schedule in Nassarawa state, Nigeria.Methodology: An explanatory mixed method design was used in which 387 parents of children aged 12 to 23 months were recruited using multistage cluster sampling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…33,40 While Munthali 36 reported that location was significant Furthermore, in this study mothers' level of education, occupation, and wealth index were significant (P < .005). This is in line with the findings of Basheer et al, 5 Adefolalu et al, 41 Konwea et al, 30 Antai, 42 Noh et al, 21 Al-lela et al, 26 Yunusa et al, 39 Bbaale, 43 Gidado et al, 44 Tagbo et al, 38 Canavan et al, 45 Feiring et al, 46 Maina et al 47 Contrastingly, the study of Bbaale, 43 did not indicate any association between the higher income of parents/caregivers and the completion of immunization schedules while Ramavhoya et al 48 and Etana and Deressa, 13 reported not significant in level of education. The difficult terrain of our study area made the work to take extra days.…”
Section: Socio-demographic Determinantssupporting
confidence: 89%
See 2 more Smart Citations
“…33,40 While Munthali 36 reported that location was significant Furthermore, in this study mothers' level of education, occupation, and wealth index were significant (P < .005). This is in line with the findings of Basheer et al, 5 Adefolalu et al, 41 Konwea et al, 30 Antai, 42 Noh et al, 21 Al-lela et al, 26 Yunusa et al, 39 Bbaale, 43 Gidado et al, 44 Tagbo et al, 38 Canavan et al, 45 Feiring et al, 46 Maina et al 47 Contrastingly, the study of Bbaale, 43 did not indicate any association between the higher income of parents/caregivers and the completion of immunization schedules while Ramavhoya et al 48 and Etana and Deressa, 13 reported not significant in level of education. The difficult terrain of our study area made the work to take extra days.…”
Section: Socio-demographic Determinantssupporting
confidence: 89%
“…At variance Basheer et al, 5 Rahman and Obaida-Nasrin, 33 Awasthi et al, 40 Adefolalu et al 41 found age to be significant. Also, Yunusa et al 39 opined that there was a significant association between the number of children and the completion of immunization. Also other studies found that parity is a very important determinant of immunization schedule completion.…”
Section: Socio-demographic Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satu orang partisipan dalam penelitian ini mengungkapkan bahwa masih belum mengerti dan tahu apa itu imunisasi serta tujuan dari imunisasi dasar itu sendiri. Partisipan tersebut terlihat bingung saat diberi pertanyaan tersebut, hal ini menunjukkan bahwa faktor pengetahuan ibu mengenai imunisasi sangat berpengaruh terhadap kelengkapan imunisasi dasar pada bayinya (Yunusa, et al, 2017).…”
Section: Pembahasanunclassified
“…Berdasarkan penelitian yang dilakukan oleh Yunusa, et al (2017) ketidakpatuhan ibu dalam pemberian imunisasi dasar dipengaruhi oleh faktor usia, tingkat pendidikan ibu persepsi penerimaan ibu, dan hambatan yang dirasakan ibu. Respon ibu yang teridentifikasi dalam penelitian ini sesuai dengan respon negatif pada ibu yang merasa khawatir dengan kondisi kesehatan bayi nya.…”
Section: Pembahasanunclassified